2020
DOI: 10.1016/j.toxicon.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment related to pinnatoxins in French shellfish

Abstract: Pinnatoxins (PnTXs) are a group of emerging marine biotoxins produced by the benthic dinoflagellate Vulcanodinium rugosum, currently not regulated in Europe or in any other country in the world. In France, PnTXs were detected for the first time in 2011, in mussels from the Ingril lagoon (South of France, Mediterranean coast). Since then, analyses carried out in mussels from this lagoon have shown high concentrations of PnTXs for several months each year. PnTXs have also been detected, to a lesser extent, in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Lamas et al (2019) found that the maximum PnTX-G levels in the South of Europe are during winter [ 11 ]. However, Arnich et al (2020) showed that PnTX-G peaks were observed between June and September from molluscs collected from the French Mediterranean coast between 2013 and 2017 [ 14 ]. Last year, because of the occurrence of PnTXs in France, the French Agency for Food, Environmental and Occupational Health and Safety has developed a scientific opinion regarding the presence of PnTXs in shellfish, setting an acceptable contamination value of 23 μg PnTX-G/kg (total meat).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lamas et al (2019) found that the maximum PnTX-G levels in the South of Europe are during winter [ 11 ]. However, Arnich et al (2020) showed that PnTX-G peaks were observed between June and September from molluscs collected from the French Mediterranean coast between 2013 and 2017 [ 14 ]. Last year, because of the occurrence of PnTXs in France, the French Agency for Food, Environmental and Occupational Health and Safety has developed a scientific opinion regarding the presence of PnTXs in shellfish, setting an acceptable contamination value of 23 μg PnTX-G/kg (total meat).…”
Section: Discussionmentioning
confidence: 99%
“…Last year, because of the occurrence of PnTXs in France, the French Agency for Food, Environmental and Occupational Health and Safety has developed a scientific opinion regarding the presence of PnTXs in shellfish, setting an acceptable contamination value of 23 μg PnTX-G/kg (total meat). Thus, a possible risk for human consumers occurs when bivalves accumulate toxins higher than this value as a result of ingesting the toxic microalgae [ 14 ]. In the present study, PnTX-G reached a maximum of 5.25 µg/kg ( M. chilensis ), much lower than the proposed level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulcanodinium rugosum is the only known producer of pinnatoxins and portimine, cyclic imine toxins considered as emergent threats to human health and challenges to the shellfish industry (Arnich et al, 2020). Pinnatoxins are neurotoxic compounds while portimine has demonstrated cytotoxic activity to mammalian cells; however no human illnesses associated with these toxinsor with any other emerging J o u r n a l P r e -p r o o f algal toxinhave been described so far (Delcourt et al, 2019;Molgó et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, symptoms following lethal dose include decrease of activity or immobility preceded of hyperactivity (except for PnTX-H), piloerection, prostration, tremors, hypothermia, jumping, hind leg extension/paralysis, abdominal breathing abruptly progressing to decrease in respiratory rate, cyanosis, exophthalmia and death (Munday et al, 2012;Selwood et al, 2010;Sosa et al, 2020). Acute toxicity, both via oral intake and i.p route, varies substantially among different pinnatoxins, being higher in PnTX-F (reviewed in Arnich et al, 2020), the dominant form in the J o u r n a l P r e -p r o o f Journal Pre-proof Cuban bloom sample. In humans, possible symptoms of PnTX intoxication via oral intake, as derived from pharmacologically similar compounds, would include the anticholinergic syndrome, pyramidal syndrome, muscle weakness, dyspnea, dysautonomia and seizures (Delcourt et al, 2019).…”
Section: Rugosum Toxinologymentioning
confidence: 99%